Implementation of coded targets for metrology applications in MicMac, a free open-source photogrammetric software - J.-M. Muller; M. Daakir; M. Pierrot Deseilligny; F. Barcet (The International Archives of the Photogrammetry, Remote Sensing and Spatial Information Sciences)
Image-based metrology is an increasingly utilized technique across a wide range of industrial applications, largely due to its reliance on precisely measurable and automatically detectable patterns within images. In photogrammetry, coded and uncoded targets, such as ground control points, are commonly used throughout the photogrammetric processing chain. This study presents recent developments in the integration of coded-targets within MicMac, a free open-source photogrammetric software. These developments were undertaken in collaboration between IGN and CERN for future accelerator alignments using image-based ecartometric measurement. One key goal, addressed in this paper, is the creation of a flexible coded-target generator within MicMac, allowing users to specify various constraints for target generation. Additionally, detection and simulation tools were implemented and evaluated. This paper focuses on the use of a common circular coded-target pattern, and introduces a novel home-made target design optimized for both image measurements and topometric instruments. Results from 2D and 3D simulations, as well as real data, demonstrate performance similar to commercial software solutions using circular coded-target, or even superior in certain configurations using our home-made target pattern. To our best knowledge, MicMac is the only free and open-source software achieving these levels of performance.